Eksplorasi Tiang Rumah Adat Kampung Manola Sumba Barat Daya - Malo, Sisilia Milla; Malli, Lukas; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The purpose of this research is to explore the meaning of the Sumbanese traditional house, not just as a dwelling, but as a cosmological symbol connecting the human world with the ancestors. The pillars are crucial elements that support the structure and serve as the center of ritual orientation. Therefore, the symbolic, structural function, and philosophical value of the pillars (parona) in the traditional house in Manola Village, South Wewewa District, Southwest Sumba Regency are examined. The research method used was qualitative with a descriptive ethnographic approach. Data were collected through field observations, architectural documentation, and in-depth interviews with traditional leaders (rato) and local craftsmen in Manola Village. The analysis focused on identifying the four main pillars (kambaniru) that play distinct roles in the spatial structure of Wewewa culture. The research results show that the exploration of the pillars of the traditional houses of Manola Village reveals a strict division of functions between masculine and feminine aspects, as well as sacred and profane. Structurally, the use of selected local wood materials demonstrates local wisdom in earthquake disaster mitigation. Symbolically, the pillars represent the vertical relationship with the creator (Maroppo-Marapu) and the horizontal relationship between clans. This study concludes that preserving the architectural details of the pillars in Manola Village is crucial in an effort to maintain Sumba's cultural identity amidst the flow of building modernization.